Bioprospecting microalga Scenedesmus obliquus as a source of lipids with anti-inflammatory and antioxidant activity - Pais, Ana Rita de Sousa (2022)
Scenedesmus obliquus is a green microalga that has in its biochemical composition a high content of omega-3 polyunsaturated fatty acids (PUFA), especially alpha-linolenic acid (ALA), which are mostly esterified to polar lipids. This is an essential fatty acid with high nutritional value that must be obtained through the diet. Omega-3 PUFA play important biological roles and health benefits, particularly in the prevention of inflammation-related non-communicable diseases. Hence, the polar lipids of Scenedesmus obliquus, rich in omega-3 PUFA, are a potential source of compounds with nutritional value, but also with potential bioactive properties. However, its polar lipid content remains scarcely explored. Therefore, the aims of the present work were (a) bioprospecting the Scenedesmus obliquus extracts obtained by dichloromethane:methanol (2:1 v/v) extraction (DCM) and with ultrasound probe-assisted ethanol extraction (EtOH+UAE) and also phospholipid + betaine- (PL+BT-) and glycolipid (GL)-enriched fractions as a source of added value polar lipids with anti-inflammatory and antioxidant properties and (b) correlate the bioactive potential of these extracts and enriched fractions with their polar lipid composition obtained using a reversed-phase liquid chromatography mass spectrometry-based untargeted lipidomics approach for a detailed identification and characterization of the extracts and fractions with anti-inflammatory and antioxidant potential. The extracts (DCM and EtOH+UAE) as well as the PL+BT- and GL-enriched fractions showed anti-inflammatory potential both in chemico through the inhibition of COX-2 activity, and in vitro by reducing the nitric oxide production and the transcription of pro-inflammatory genes, including Il1β, Ptgs2, Tnfα and Nos2 in lipopolysaccharide-stimulated macrophages. Besides, the extracts and fractions under study also showed antioxidant potential, being able to scavenge the ABTS●⁺ and DPPH● radicals in chemico, and to reduce intracellular oxidative stress in vitro, in Jurkat lymphocytes treated with tert-butyl hydroperoxide. Overall, the EtOH+UAE extract and PL+BT-enriched fraction demonstrated to have better anti-inflammatory activity, while DCM demonstrated better antioxidant activity. Results gathered in this study suggested that the composition of the extracts/fractions is very relevant for their biological activities, that the EtOH-UAE extracts, obtained with a green food-grade solvent, are a source of bioactive compounds, and that PL+BT- and GL-enriched fractions play a relevant key role in the bioactive potential demonstrated by the EtOH+UAE extracts. The characterization of the lipid extracts by C18-RP-LC-ESI-MS/MS showed that S. obliquus biomass is a very interesting source of bioactive polar lipids, rich in omega-3 PUFA, and even in EPA, thus contributing to its valorisation. Future studies are needed to unveil the bioaccessibility and bioavailability of the potential bioactive lipid species present in the extracts and enriched fractions of S. obliquus to ensure their efficacy in the health and functional claims.